Process Monitoring for the Exponentially Distributed Characteristics through an Optimal Normalizing Transformation - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2000)
Many process characteristics follow an exponential distribution, and control charts based on such a distribution have attracted a lot of attention. However, traditional control limits may be not appropriate because of the lack of symmetry. In this paper, process monitoring through a normalizing power transformation is studied.